Language Representation Features of Primary Human Needs in Discourse: a Case Study on Short Prose by A. Solzhenitsyn - Statsenko, Olena (Respectus Philologicus, 2021)
The article is devoted to the cognitive analysis of linguistic means, representing the primary human needs in extreme conditions. The nominations denoting the concepts of “food” and “warmth” are subjected to the lexico-semantic, grammatical, stylistic consideration. A choice of the discourse for analysis is due to describing a human life in detention when the primary adaptive needs prevail all others and become the most valuable. The representation of human basic biological need in food and warmth is considered in the given contexts. The use of colloquial vocabulary, grammatical norms violation, as well as figurative comparisons and transformed phraseological units in the contexts determine peculiarities of the verbal explication of the concept “food”. The author pays attention to the stylistically reduced vocabulary, which stands out the lexeme “belly”, acquiring new semantic shades in the analyzed fragments. With the nomination of warmth as another important human need for existence, the lexeme “stove” is associated. The paper identifies and analyzes the factors that cause the life values changes at the cognitive level of a person experiencing deprivation of basic biological needs.